Chronic hepatitis C viral infection subverts vaccine‐induced T‐cell immunity in humans. Issue 5 (22nd January 2016) - Kelly, Christabel; Swadling, Leo; Capone, Stefania; Brown, Anthony; Richardson, Rachel; Halliday, John; von Delft, Annette; Oo, Ye; Mutimer, David; Kurioka, Ayako; Hartnell, Felicity; Collier, Jane; et al.
Abstract : Adenoviral vectors encoding hepatitis C virus (HCV) nonstructural (NS) proteins induce multispecific, high‐magnitude, durable CD4 + and CD8 + T‐cell responses in healthy volunteers. We assessed the capacity of these vaccines to induce functional HCV‐specific immune responses and determine T‐cell cross‐reactivity to endogenous virus in patients with chronic HCV infection. HCV genotype 1‐infected patients were vaccinated using heterologous adenoviral vectors (ChAd3‐NSmut and Ad6‐NSmut) encoding HCV NS proteins in a dose escalation, prime‐boost regimen, with and without concomitant pegylated interferon‐α/ribavirin therapy. Analysis of immune responses ex vivo used human leukocyte antigen class I pentamers, intracellular cytokine staining, and fine mapping in interferon‐γ enzyme‐linked immunospot assays. Cross‐reactivity of T cells with population and endogenous viral variants was determined following viral sequence analysis. Compared to healthy volunteers, the magnitude of HCV‐specific T‐cell responses following vaccination was markedly reduced. CD8 + HCV‐specific T‐cell responses were detected in 15/24 patients at the highest dose, whereas CD4 + T‐cell responses were rarely detectable. Analysis of the host circulating viral sequence showed that T‐cell responses were rarely elicited when there was sequence homology between vaccine immunogen and endogenous virus. In contrast, T cells were induced in the context of genetic mismatch between vaccine immunogen and endogenous virus; however, these commonly failed to recognize circulating epitope variants and had a distinct partially functional phenotype. Vaccination was well tolerated but had no significant effect on HCV viral load. Conclusion: Vaccination with potent HCV adenoviral vectored vaccines fails to restore T‐cell immunity except where there is genetic mismatch between vaccine immunogen and endogenous virus; this highlights the major challenge of overcoming T‐cell exhaustion in the context of persistent antigen exposure with implications for cancer and other persistent infections. (Hepatology 2016;63:1455‐1470)